Production of ammonia feedstock by novel solid oxide electrolysis cell - Haziq Mahmud (Nanyang Technological University, 2021)
Ammonia would play a significant role in the future hydrogen economy. Currently, the predominant industrial route for ammonia synthesis is the Haber Bosch process which is a very laborious and energy intensive process. Today, energy consumption for ammonia synthesis is about 1.4% of all the energy consumed worldwide. Natural gas or coal is used as the energy source of the ammonia industry. In addition, the hydrogen feedstock required is mostly from steam reforming of natural gas. Due to very complicated procedure, the conventional Haber osch process also produces large quantities of CO2 emissions and has remarkable adverse influences on the environment. Hence, it is necessary to develop an alternative process or improve the current Haber Bosch process for renewable/low carbon and energy efficient synthesis of ammonia. This project aims to explore the efficient and renewable production of ammonia feedstock which is a mixture of N2 and H2 through a high temperature SOEC system. In this project, wet air co-electrolysis experiments using SOEC were conducted to produce the mixture of N2 and H2. The SOEC cells had a symmetrical configuration. The material of the electrolyte is Yttria stabilized Zirconia (YSZ). The electrode material is made up of La0.75Sr0.25Cr0.5Mn0.5O3 (LSCM) and Gadolinium doped ceria (GDC), amix of electronic and ionic conductors which comes from LSCM and GDC, respectively. To improve the electrodeactivity and cell performance, Ni dopant was also used in the synthesis of LSCM powders. The wet air co-electrolysis behaviours of the cells were examined carefully under various operation conditions. More importantly, a novel SOEC operation mode was investigated in order to enhance the wet air co-electrolysis reaction at the fuel electrode. Some interesting results have been obtained from the experimental investigations. Electrochemical characterisation results from the cells show a general trend of an increase in current density with increasing air inlet flowrate for fuel electrode, an increase in cell performance with increasing water vapour percentage due to more water electrolysis occurring, better cell performance achieved with methane or 50% CH4/ 50% N2 mixture as an inlet gas to air electrode chamber as compared to air, showing the advantage of the Novel SOEC mode over conventional SOEC mode, an increase in current density and reduction in resistance values with increasing operating temperatures and the use of a nickel dopant in LSCM which significantly enhanced the cell performance in both the conventional SOEC mode and novel SOEC mode. Although there are improvements in the cell performance, the overall cell performance was still not good enough compared with published results in the literature. Hence, the electrode performance must be enhanced in order to be considered for the use for ammonia production.